Electroacupuncture regulates ferroptosis to improve postoperative cognitive dysfunction in mice through mediating GRX1/GSK-3β/Nrf2 axis - Xiaqing Zhang; Afen Zhang; Rui Li; Mingna Jiao; Rou Wen; Rongzhi Zheng (Brain Research Bulletin)
Background: The incidence of postoperative cognitive dysfunction (POCD) is higher happening in the elderly. It has been reported electroacupuncture (EA) was beneficial to the treatment of POCD, but its specific regulatory mechanism is still unclear. Methods: Through partial hepatectomy in mice, POCD model of mice was established. Baihui acupoint (GV20) was selected for targeted point of EA therapy. Morris water maze (MWM) was applied to evaluate cognitive impairment of mice. HE staining was used to examine cell arrangement and cell morphology in hippocampus of mice. RT-qPCR, western blot and IHC were employed to detect abundance of genes and proteins. MDA, GSH and iron levels was measured by some commercial kits. Results: Our findings revealed that partial hepatectomy surgery impaired learning and memory ability of mice, promoted ferroptosis. inhibited GRX1 and inactivated GSK-3β/Nrf2 pathway. However, EA therapy abolished these effects. In addition, GRX1 silencing and erastin abolished EA-mediated alterations of improving POCD in mice. Conclusion: EA suppressed ferroptosis by regulating GRX1/GSK-3β/Nrf2 pathway to improve postoperative cognitive dysfunction of POCD mice.